An autoclaved-free phc pipe pile application concrete and a preparation method thereof

CN122749020APending Publication Date: 2026-09-15URUMQI TOUTUNHE BAGANG DUOJING STEEL DREGS FACTORY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610919814.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-09-15

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种免蒸压PHC管桩应用混凝土及其制备方法,以解决现有技术下传统PHC管桩生产采用高压蒸压工艺,导致能耗与碳排放高、生产成本高且产品质量不稳定的问题

Benefits of technology

[0008] The beneficial effects of the present invention are as follows: (1) The present invention constructs a full-chain synergistic regulation system of nucleation acceleration-rapid hydration-moisturization-structural compaction-thermal insulation and temperature locking, and forms corresponding composite early strength components, dual internal curing mechanism and step-by-step mixing process, thereby achieving rapid early strength development, thereby improving the durability and construction adaptability of concrete in harsh environments such as low temperature and dryness; (2) By eliminating the traditional 180℃ high temperature autoclaving process, strength development is achieved by relying on the composite early strength system and self-curing, reducing energy consumption by 59-64% and carbon emissions by 54-59%, significantly reducing coal consumption and production costs; (3) By dispersing the nucleation carrier, controlling the release of water by core-shell SAP, dual internal curing and step-by-step mixing, the problems of nano-component aggregation and functional material failure are solved; and it can be directly produced using existing pipe pile equipment, with stable quality and easy to scale up.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1782275180084-000001
    Figure REF-OBJ-1782275180084-000001
  • Figure REF-OBJ-1782275180084-000002
    Figure REF-OBJ-1782275180084-000002
Patent Text Reader

Abstract

The application belongs to the technical field of building materials, and specifically discloses a kind of steam-free pressure PHC pipe pile application concrete, raw materials include P·O52.5 grade Portland cement, S105 grade slag powder, I grade fly ash, silica fume, gravel and II area medium sand, C-S-H crystal seed, nano CaCO3, CSA clinker powder and calcium formate, salt-loaded SAP, pre-wet light fine aggregate, and mixing water and polycarboxylic acid water reducing agent.Aiming at the problem that the current traditional PHC pipe pile production adopts high-pressure autoclaving process, resulting in high energy consumption, the application realizes nucleation acceleration, rapid hydration, moisture slow release, structure densification, heat preservation and temperature locking synergistic regulation and control, and cancels the traditional high-temperature autoclaving process, improves the mechanical properties and durability of the concrete, and at the same time, reduces the production energy consumption and carbon emission, solves the problem that the traditional PHC pipe pile production in the prior art adopts high-pressure autoclaving process, resulting in high energy consumption and carbon emission, high production cost and unstable product quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, specifically to a non-autoclaved PHC pipe pile application concrete and its preparation method. Background Technology

[0002] Prestressed high-strength concrete pipe piles (PHC pipe piles) are widely used in various foundation engineering fields such as building construction, municipal roads, bridges and wharves, and rail transit due to their advantages of high bearing capacity, strong integrity, and convenient construction. They are one of the most widely used and mature precast building material components in pile foundation engineering. With the large-scale development of infrastructure and the continuous promotion of green and low-carbon industrial policies in my country, the building materials industry has put forward higher standards for the production energy efficiency, environmental performance, production cost, and product quality stability of PHC pipe piles. The shortcomings and limitations of traditional production processes are becoming increasingly prominent, and they are no longer able to meet the industry's development needs for high quality, low carbon, and low cost.

[0003] Currently, the standardized production of conventional PHC pipe piles generally adopts a two-stage curing process of "atmospheric pressure steam curing + high-pressure steam curing." Its core relies on the high-pressure steam curing process to achieve rapid concrete curing and strength attainment, meeting the requirements for pipe pile delivery and engineering construction. However, the high-pressure steam curing process requires the continuous consumption of fuels such as coal, fuel oil, and natural gas to generate high-temperature, high-pressure steam. Furthermore, the operation of the autoclave and the entire process of heating and cooling require continuous electricity consumption, resulting in extremely high overall energy consumption. Although this production model has been able to basically guarantee the mechanical properties of pipe pile foundations after long-term application, it suffers from technical defects such as high energy consumption and carbon emissions, high production costs, and poor product quality stability. These have become core issues restricting the green upgrading and quality improvement of the PHC pipe pile industry.

[0004] The extreme curing environment of high pressure and high temperature accelerates the cement hydration reaction of concrete, causing the rapid formation of coarse crystalline structures within the concrete, leading to an imbalance in the crystal-cement ratio, increased brittleness, and insufficient toughness of the concrete matrix. Simultaneously, the heating and cooling rates during autoclaving are difficult to control precisely and uniformly, easily generating thermal stress and shrinkage stress inside and outside the pipe pile wall. This induces defects such as internal micro-cracks, surface loosening, and aggregate segregation, which not only reduce the bending, cracking, and compressive mechanical properties of the pipe pile but also cause significant fluctuations in strength, density, and durability parameters among different batches and specifications, resulting in poor product consistency. Furthermore, high-pressure autoclaved concrete is prone to carbonation and decreased impermeability during long-term use, significantly shortening the service life of the pipe piles, increasing the risks and costs of later-stage operation and maintenance, and failing to meet the high stability and durability requirements of high-end infrastructure and complex geological engineering for pile foundation components.

[0005] In summary, it is necessary to design a non-autoclaved PHC pipe pile application concrete and its preparation method to solve the problems of high energy consumption and carbon emissions, high production costs and unstable product quality caused by the high-pressure autoclaving process used in the production of traditional PHC pipe piles under the existing technology. Summary of the Invention

[0006] The purpose of this invention is to provide a non-autoclaved PHC pipe pile application concrete and its preparation method, so as to solve the problems of high energy consumption and carbon emissions, high production costs and unstable product quality caused by the high-pressure autoclaving process used in the production of traditional PHC pipe piles under the existing technology.

[0007] To achieve the above objectives, the basic solution provided by this invention is as follows: a non-autoclaved PHC pipe pile concrete, the raw materials of which include cementitious materials, aggregates, composite early-strength components, dual internal curing components, mixing water, and admixtures; the cementitious materials, by mass percentage, include: 50-60% P·O52.5 grade silicate cement, 20-30% S105 grade slag powder, 10-20% grade I fly ash, and 5-8% silica fume; the aggregates include coarse aggregates and fine aggregates, wherein the coarse aggregates are 5-20mm continuously graded crushed stone, accounting for 40-45%, and the fine aggregates are zone II fineness modulus of 2.6-3.0. The sand content is 25-30%; the composite early strength component, based on the total amount of cementitious materials, includes: 0.2-0.8% CSH seed crystals, 0.5-2.0% nano-CaCO3, 3-8% CSA clinker powder, and 0.5-1.5% calcium formate; the dual internal curing component, based on the total amount of cementitious materials, includes: 0.10-0.25% salt-loaded SAP and 5-12% pre-wetted lightweight fine aggregate to replace natural sand; the mixing water is tap water or clean reclaimed water, with a water-cement ratio of 0.22-0.28; the admixture is polycarboxylate superplasticizer, accounting for 0.8-1.5% of the total amount of cementitious materials.

[0008] The beneficial effects of the present invention are as follows: (1) The present invention constructs a full-chain synergistic regulation system of nucleation acceleration-rapid hydration-moisturization-structural compaction-thermal insulation and temperature locking, and forms corresponding composite early strength components, dual internal curing mechanism and step-by-step mixing process, thereby achieving rapid early strength development, thereby improving the durability and construction adaptability of concrete in harsh environments such as low temperature and dryness; (2) By eliminating the traditional 180℃ high temperature autoclaving process, strength development is achieved by relying on the composite early strength system and self-curing, reducing energy consumption by 59-64% and carbon emissions by 54-59%, significantly reducing coal consumption and production costs; (3) By dispersing the nucleation carrier, controlling the release of water by core-shell SAP, dual internal curing and step-by-step mixing, the problems of nano-component aggregation and functional material failure are solved; and it can be directly produced using existing pipe pile equipment, with stable quality and easy to scale up.

[0009] Option 2, the preferred option of the basic option, requires a specific surface area of ​​S105 grade slag powder ≥ 500 m². 2 / kg, Grade I fly ash residue on a 45μm sieve ≤12%, silica fume specific surface area ≥20000m² 2 / kg, SiO2 content in silica fume ≥90%, crushing index of coarse aggregate ≤8%, average particle size of CSH seeds 100-500nm, solid content ≥30%, specific surface area of ​​nano-CaCO3 ≥800m² 2 / kg, CSA clinker powder with a specific surface area ≥450m² 2 / kg, initial setting time ≥25min, calcium formate purity ≥98%, salt-loaded SAP water absorption ratio ≥20g / g in 0.5%~5% CaCl2 solution, pre-wetted lightweight fine aggregate is ceramic sand or zeolite sand with 24h water absorption rate ≥15%, polycarboxylate superplasticizer water reduction rate ≥30%, solid content ≥40%. Clearly define the performance indicators of concrete raw materials to ensure high quality and high activity of nano-components, cementitious materials, admixtures, and aggregates.

[0010] Option 3, a method for preparing concrete for non-autoclaved PHC pipe piles, includes the following steps: S1: Preparation of nucleated carrier-based early strength slurry: First, take 10-20% of the total amount of S105 grade slag powder or grade I fly ash as carrier powder. Then, mix CSH seed crystals, nano CaCO3 with water-reducing agent and part of mixing water using a high-speed disperser. Then add the carrier powder and continue mixing so that the nanoparticles are uniformly attached to the surface of the carrier powder. S2: Preparation of salt environment responsive SAP microgels: First, polyacrylic acid SAP particles are impregnated in sodium alginate solution, then crosslinked and cured with a mixed solution containing 2-4% CaCl2 and 1-3% silica sol. Next, the surface free salts are removed by washing with water, and then dried to obtain polyacrylic acid SAP microgel particles. S3: Lightweight aggregate pre-wetting and interface strengthening treatment: First, soak the lightweight fine aggregate in clean water and drain it until it is saturated and surface dry. Then, mix the saturated surface dry lightweight fine aggregate with S105 grade slag powder and silica fume to make the S105 grade slag powder and silica fume evenly coat the surface of the lightweight fine aggregate to form a dual-function aggregate. S4: Mixing: First, add crushed stone, natural sand and bifunctional aggregate to the mixer and mix for 30 seconds. Then add the nucleating and reinforcing slurry prepared in S1, the remaining cementitious material and the remaining mixing water and continue mixing for 60-90 seconds. Then add the polyacrylic acid SAP microgel particles prepared in S2 and mix for 30-45 seconds before discharging from the mixer to obtain the non-autoclaved PHC pipe pile concrete.

[0011] By preparing nucleated carrier-based early-strength slurry, modifying SAP core-shell, strengthening the interface of lightweight aggregate, and three-stage mixing, the problems of easy agglomeration and uneven dispersion of nano-components were solved; controlled release of water from SAP was achieved, avoiding early water grabbing and later failure, while improving the density and durability of concrete.

[0012] Option 4, an optimal choice of Option 3, involves the following steps in S1: Based on the total amount of cementitious materials, the mass percentage of CSH seed crystals is 0.2-0.8%, the mass percentage of nano-CaCO3 is 0.5-2.0%, and the mixing water accounts for 30-50% of the total water volume. The high-speed disperser operates at 800-1200 rpm, and the stirring time is 2-3 minutes. After adding the carrier powder, stirring continues for 1-2 minutes. This ensures complete deagglomeration of the nanoparticles, and the carrier adsorption process also enables uniform distribution of the nano-components, resulting in stable early strength. Simultaneously, precise water proportioning further enhances the stability of the slurry.

[0013] Option 5, a preferred option of Option 3, involves using polyacrylic acid SAP particles with a particle size of 0.1-0.5 mm in S2. The mass ratio of polyacrylic acid SAP particles to sodium alginate solution is 1:10-1:20, the mass fraction of the sodium alginate aqueous solution is 1.0-2.0%, the impregnation time is 10-20 min, the curing time is 3-8 min, the drying temperature is 45-55℃, and the drying time is 8-12 h. By forming a core-shell structured SAP microgel, precise controlled water release can be achieved under highly alkaline conditions. Reasonable washing and drying parameters can prevent the agglomeration of polyacrylic acid SAP particles and shell damage.

[0014] Option 6, an optimal choice from Option 3, involves using S105 grade slag powder and silica fume as admixtures, where the mass percentage of these admixtures is 5-10% of the total remaining admixtures, and the mixing time is 30-45 seconds. The ultrafine powders (slag powder and silica fume) coat the lightweight aggregate, densifying the interfacial transition zone, improving the bond strength between the aggregate and the slurry, reducing microcracks, and thus simultaneously achieving both internal curing and interfacial enhancement.

[0015] Option 7, a preferred option of Option 3, involves adding 50-70% of the total water volume in step S4, 0.10-0.25% of the total cementitious material volume of polyacrylic acid SAP microgel particles, and a total stirring time of 120-180 seconds. Controlling the total stirring time balances uniformity and efficiency, while adding the SAP microgel later during stirring helps protect the core-shell structure from shear damage. Detailed Implementation

[0016] The present invention will be further described in detail below through specific embodiments: Example 1

[0017] A method for preparing concrete for non-autoclaved PHC pipe piles includes the following steps: S1: Preparation of nucleation-carrier-based early-strength slurry: First, select 15% of the total amount of S105 grade slag micro powder as carrier powder. Then, mix 0.5% CSH seed crystals, 1.2% nano-CaCO3, 1.2% water-reducing agent, and 50% of the total water volume with mixing water. Then, stir the mixture for 3 minutes at 1000 rpm using a high-speed disperser to fully deaggregate and uniformly suspend the nanoparticles. Then, add the carrier powder to the suspension and continue to disperse for 1.5 minutes to ensure that the nanoparticles are uniformly attached to the surface of the carrier powder, thus obtaining the nucleation-enhanced slurry. S2: Preparation of Salt-Responsive SAP Microgels: First, 1 part of polyacrylic acid SAP particles with a particle size of 0.1-0.5 mm was immersed in 15 parts of a 1.5% sodium alginate aqueous solution for 15 min, allowing the sodium alginate macromolecules to penetrate into the surface network of the polyacrylic acid SAP particles. Then, the polyacrylic acid SAP particles were removed from the leachate and subsequently added to a mixed solution containing 3% CaCl2 and 2% silica sol for cross-linking and curing. The mixed solution consisted of 15 parts, and the curing time was 5 min, allowing the CaCl2 to penetrate into the surface network of the polyacrylic acid SAP particles. 2+ A calcium alginate gel shell is formed by cross-linking with sodium alginate, while silica sol fills the gel network and combines with it to form a dense polysaccharide-inorganic composite shell, thus obtaining polyacrylic acid SAP microgel particles. After cross-linking, the polyacrylic acid SAP microgel is washed with water to remove free salts on the surface, and then dried at 50°C for 10 hours to obtain polyacrylic acid SAP microgel particles with a core-shell structure. S3: Lightweight aggregate pre-wetting and interface strengthening treatment: First, soak 50kg of ceramic sand in clean water for 24 hours in advance, then take it out and drain it until it is saturated and surface dry. Then take 8% of the remaining S105 grade slag powder and silica powder admixture. Then use a mixer to premix the saturated surface dry ceramic sand with the S105 grade slag powder and silica powder admixture at low speed for 45 seconds, so that the ultrafine powder (including S105 grade slag powder and silica powder) is evenly coated on the surface of the lightweight fine aggregate, forming a dual-function aggregate with internal curing and interface strengthening. S4: Mixing: First, add 1000kg of crushed stone, 620kg of natural sand, and the pretreated bifunctional aggregate to the mixer in sequence, and dry mix for 30s to make the aggregate evenly mixed. Then, add the nucleating and reinforcing slurry prepared in S1, and add the remaining cementitious materials (including 286kg of P·O52.5 grade silicate cement, 110.5kg of S105 grade slag powder, 78kg of grade I fly ash, and 26kg of silica fume) and 50% of the total water volume of mixing water, and mix for 75s to make the nucleus-rich slurry fully coat the aggregate. Then, add 0.94kg of polyacrylic acid SAP microgel particles prepared in S2, and continue mixing for 40s before discharging from the machine. The resulting mix proportion is: (based on a total cementitious material content of 100%, the total cementitious material content is taken as 520 kg / m³). 3 The concrete contains 55% (286kg) of P·O52.5 grade silicate cement, 25% (130kg) of S105 grade slag powder, 15% (78kg) of grade I fly ash, 5% (26kg) of silica fume, and (in percentage of total cementitious materials) 0.5% (2.6kg) of CSH seed crystals, 1.2% (6.2kg) of nano CaCO3, 6.0% (31.2kg) of CSA clinker powder, 1.0% (5.2kg) of calcium formate, 0.18% (0.94kg) of salt-loaded SAP microgel, 1.2% (6.2kg) of polycarboxylate superplasticizer, 1000kg of 5-20mm continuously graded crushed stone, 620kg of zone II medium sand (fineness modulus 2.8), 50kg of pre-wetted zeolite sand (replacing 8% of natural sand), and 125kg of water, with a water-cement ratio of 0.24.

[0018] Finally, the concrete prepared in S4 is poured into the steel mold for the pipe pile, and the PHC pipe pile is formed by centrifugation at a speed of 1000 rpm. The formed PHC pipe pile is then immediately covered with a plastic film, left to stand for 2 hours, and then demolded. After demolding, the PHC pipe pile is covered with heat-insulating and moisture-retaining material and naturally cured for 7 days at a temperature ≥15℃. When the ambient temperature is between 5-15℃, the heat-insulating covering is strengthened, and the self-steaming curing effect is achieved by utilizing the heat of hydration of the concrete itself.

[0019] Example 2

[0020] A method for preparing concrete for non-autoclaved PHC pipe piles, the steps of which are the same as those in Example 1, the difference being: S1: Preparation of nucleation-carrier-based early-strength slurry: First, select 20% of the total amount of Grade I fly ash as carrier powder. Then, mix 0.4% CSH seed crystals, 1.0% nano-CaCO3, 1.15% polycarboxylate superplasticizer, and 50% of the total water volume of mixing water. Then, stir the mixture for 3 minutes at 1000 rpm using a high-speed disperser. Finally, add the carrier powder to the suspension and continue to disperse for 1.5 minutes to obtain the nucleation-reinforced slurry. S3: Lightweight aggregate pre-wetting and interface strengthening treatment: First, soak 61kg of zeolite sand in clean water for 24 hours in advance, then take it out and drain it until it is saturated and dry. Then take 8% of the remaining S105 grade slag powder and silica powder admixture. Then use a mixer to premix the saturated and dry zeolite sand with the S105 grade slag powder and silica powder admixture at low speed for 45 seconds. S4: Step-by-step mixing: First, add 1020kg of crushed stone, 610kg of natural sand, and pretreated zeolite sand to the mixer in sequence and dry mix for 30s. Then, add the nucleating and reinforcing slurry prepared in S1, and add the remaining cementitious materials (260kg of P·O52.5 grade silicate cement, 110kg of S105 grade slag powder, 80kg of grade I fly ash, and 30kg of silica fume) and 50% of the total water volume of mixing water and mix for 75s. Then, add 1.0kg of polyacrylic acid SAP microgel particles prepared in S2, continue mixing for 40s, and then discharge from the machine. The resulting mix proportion is: (based on a total cementitious material content of 100%, with a total cementitious material content of 500 kg / m³). 3 The concrete contains 52% (260kg) of P·O52.5 grade silicate cement, 26% (130kg) of S105 grade slag powder, 16% (80kg) of grade I fly ash, 6% (30kg) of silica fume, and (in percentage of total cementitious materials) 0.4% (2.0kg) of CSH seed crystals, 1.0% (5.0kg) of nano CaCO3, 5.0% (25.0kg) of CSA clinker powder, 0.8% (4.0kg) of calcium formate, 0.20% (1.0kg) of salt-loaded SAP microgel, 1.15% (5.75kg) of polycarboxylate superplasticizer, 1020kg of 5-20mm continuously graded crushed stone, 610kg of zone II medium sand (fineness modulus 2.7), 61kg of pre-wetted zeolite sand (replacing 10% of natural sand), and 130kg of water, with a water-cement ratio of 0.26.

[0021] Example 3

[0022] A method for preparing concrete for non-autoclaved PHC pipe piles, the steps of which are the same as those in Example 1, the difference being: S1: Preparation of nucleation-carrier early-strength slurry: First, select 10% of the total amount of S105 grade slag powder as carrier powder. Then, mix 0.2% CSH seed crystals, 0.5% nano CaCO3, 1.1% water-reducing agent, and 50% of the total water volume with mixing water. Then, stir for 3 minutes using a high-speed disperser. Finally, add the carrier powder to the suspension and continue to disperse for 1.5 minutes. S3: Lightweight aggregate pre-wetting and interface strengthening treatment: First, soak 72kg of ceramic sand in clean water for 24 hours in advance, then take it out and drain it until it is saturated and dry. Then take 8% of the remaining S105 grade slag powder and silica powder admixture. Then use a mixer to premix the saturated and dry ceramic sand with the S105 grade slag powder and silica powder admixture at low speed for 45 seconds. S4: Mixing: First, add 1040kg of crushed stone, 600kg of natural sand, and pretreated ceramic sand to the mixer in sequence and dry mix for 30s. Then, add the nucleating and reinforcing slurry prepared in S1, and add the remaining cementitious materials (including 240kg of P·O52.5 grade silicate cement, 99kg of S105 grade slag powder, 96kg of grade I fly ash, and 34kg of silica fume) and mix for 75s. Then, add 1.2kg of polyacrylic acid SAP microgel particles prepared in S2, continue mixing for 40s, and then discharge from the machine. The resulting mix proportion is: (based on a total cementitious material content of 100%, the total cementitious material content is taken as 480 kg / m³). 3 Concrete with a water-cement ratio of 0.28, consisting of 50% (240kg) P·O52.5 grade silicate cement, 23% (110kg) S105 grade slag powder, 20% (96kg) grade I fly ash, 7% (34kg) silica fume, 0.2% (0.96kg) CSH seed crystals, 0.5% (2.4kg) nano CaCO3, 4.0% (19.2kg) CSA clinker powder, 0.5% (2.4kg) calcium formate, 0.25% (1.2kg) salt-loaded SAP microgel, 1.1% (5.28kg) polycarboxylate superplasticizer, 1040kg 5-20mm continuously graded crushed stone, 600kg Zone II medium sand (fineness modulus 2.9), 72kg pre-wetted zeolite sand (replacing 12% of natural sand), and 134kg water.

[0023] Example 4

[0024] A method for preparing concrete for non-autoclaved PHC pipe piles, the steps of which are the same as those in Example 1, the difference being: S1: The preparation of nucleation carrier-based early strength slurry is cancelled, and CSH seed crystals, nano CaCO3, and polycarboxylate superplasticizer are not pre-stirred or carrier adsorbed. S3: Lightweight aggregate pre-wetting and interface strengthening treatment: First, soak 50kg of ceramic sand in clean water for 24 hours in advance, then take it out and drain it until it is saturated and surface dry. Then take 8% of the remaining S105 grade slag powder and silica powder admixture. Then use a mixer to premix the saturated surface dry ceramic sand with the S105 grade slag powder and silica powder admixture at low speed for 45 seconds, so that the ultrafine powder (including S105 grade slag powder and silica powder) is evenly coated on the surface of the lightweight fine aggregate, forming a dual-function aggregate with internal curing and interface strengthening. S4: Mixing: First, add 1000kg of crushed stone, 620kg of natural sand, and the pretreated bifunctional aggregate to the mixer in sequence, and dry mix for 30s to make the aggregate evenly mixed. Then, add the remaining cementitious materials (including 286kg of P·O52.5 grade silicate cement, 130kg of S105 grade slag powder, 78kg of grade I fly ash and 26kg of silica fume), 2.6kg of C-SH seed crystals, 6.2kg of nano CaCO3, 31.2kg of CSA clinker powder, 5.2kg of calcium formate, 6.2kg of polycarboxylate superplasticizer, and 125kg of mixing water to the mixer and mix for 90s. Then, add 0.94kg of polyacrylic acid SAP microgel particles prepared in S1, continue mixing for 40s, and then discharge from the machine. The resulting mix proportion is: (based on a total cementitious material content of 100%, the total cementitious material content is taken as 520 kg / m³). 3 The concrete contains 55% (286kg) of P·O52.5 grade silicate cement, 25% (130kg) of S105 grade slag powder, 78% (96kg) of grade I fly ash, 5% (26kg) of silica fume, and (in percentage of total cementitious materials) 0.5% (2.6kg) of CSH seed crystals, 1.2% (6.2kg) of nano CaCO3, 6.0% (31.2kg) of CSA clinker powder, 1.0% (5.2kg) of calcium formate, 0.18% (0.94kg) of salt-loaded SAP microgel, 1.2% (6.2kg) of polycarboxylate superplasticizer, 1000kg of 5-20mm continuously graded crushed stone, 620kg of zone II medium sand (fineness modulus 2.8), 50kg of pre-wetted zeolite sand (replacing 8% of natural sand), and 125kg of water, with a water-cement ratio of 0.24.

[0025] Example 5

[0026] A method for preparing concrete for non-autoclaved PHC pipe piles, the steps of which are the same as those in Example 1, the difference being: S1: Preparation of nucleation-carrier-based early-strength slurry: First, select 15% of the total amount of S105 grade slag micro powder as carrier powder. Then, mix 0.5% CSH seed crystals, 1.2% nano-CaCO3, 1.2% water-reducing agent, and 50% of the total water volume with mixing water. Then, stir the mixture for 3 minutes at 1000 rpm using a high-speed disperser to fully deaggregate and uniformly suspend the nanoparticles. Then, add the carrier powder to the suspension and continue to disperse for 1.5 minutes to ensure that the nanoparticles are uniformly attached to the surface of the carrier powder, thus obtaining the nucleation-enhanced slurry. S2: Cancel the preparation of salt-responsive SAP microgels; S3: Cancel the pre-wetting and interface strengthening treatment of lightweight aggregates; S4: Mixing: First, add 1000kg of crushed stone and 670kg of natural sand to the mixer and dry mix for 30s. Then, add the nucleating and reinforcing slurry prepared in S1, and add the remaining cementitious materials (including 286kg of P·O52.5 grade silicate cement, 110.5kg of S105 grade slag powder, 78kg of grade I fly ash and 26kg of silica fume), 31.2kg of CSA clinker powder, 5.2kg of calcium formate, and 50% of the total water volume of mixing water. Mix for 75s to ensure that the nucleus-rich slurry fully coats the aggregate. Continue mixing for 40s and then remove from the machine. The resulting mix proportion is: (based on a total cementitious material content of 100%, the total cementitious material content is taken as 520 kg / m³). 3 The concrete contains 55% (286kg) of P·O52.5 grade silicate cement, 25% (130kg) of S105 grade slag powder, 78% (96kg) of grade I fly ash, 5% (26kg) of silica fume, and (in percentage of total cementitious materials) 0.5% (2.6kg) of CSH seed crystals, 1.2% (6.2kg) of nano CaCO3, 6.0% (31.2kg) of CSA clinker powder, 1.0% (5.2kg) of calcium formate, 0.18% (0.94kg) of salt-loaded SAP microgel, 1.2% (6.2kg) of polycarboxylate superplasticizer, 1000kg of 5-20mm continuously graded crushed stone, 620kg of zone II medium sand (fineness modulus 2.8), 50kg of pre-wetted zeolite sand (replacing 8% of natural sand), and 125kg of water, with a water-cement ratio of 0.24.

[0027] Example 6

[0028] A method for preparing concrete for non-autoclaved PHC pipe piles, the steps of which are the same as those in Example 1, the difference being: S2: Polyacrylic acid SAP particles with a particle size of 0.1-0.5mm and a water absorption ratio of ≥200g / g are selected. They are not pre-impregnated with sodium alginate or subjected to ion crosslinking and curing treatment, and have no core-shell structure. S3: Lightweight aggregate pre-wetting and interface strengthening treatment: First, soak 50kg of ceramic sand in clean water for 24 hours in advance, then take it out and drain it until it is saturated and surface dry. Then take 8% of the remaining S105 grade slag powder and silica powder admixture. Then use a mixer to premix the saturated surface dry ceramic sand with the S105 grade slag powder and silica powder admixture at low speed for 45 seconds, so that the ultrafine powder (including S105 grade slag powder and silica powder) is evenly coated on the surface of the lightweight fine aggregate, forming a dual-function aggregate with internal curing and interface strengthening. S4: Mixing: First, add 1000kg of crushed stone, 620kg of natural sand, and the pretreated bifunctional aggregate to the mixer in sequence, and dry mix for 30s to make the aggregate evenly mixed. Then, add the nucleating and reinforcing slurry prepared in S1, and add the remaining cementitious materials (including 286kg of P·O52.5 grade silicate cement, 110.5kg of S105 grade slag powder, 78kg of grade I fly ash and 26kg of silica fume), 31.2kg of CSA clinker powder and 5.2kg of calcium formate and mix for 75s. Then, add 0.94kg of polyacrylic acid SAP particles from S2, continue mixing for 40s and then discharge from the machine. The resulting mix proportion is: (based on a total cementitious material content of 100%, the total cementitious material content is taken as 520 kg / m³). 3 The concrete contains 55% (286kg) of P·O52.5 grade silicate cement, 25% (130kg) of S105 grade slag powder, 15% (78kg) of grade I fly ash, 5% (26kg) of silica fume, and (as a percentage of the total cementitious materials) 0.5% (2.6kg) of CSH seed crystals, 1.2% (6.2kg) of nano CaCO3, 6.0% (31.2kg) of CSA clinker powder, 1.0% (5.2kg) of calcium formate, 0.18% (0.94kg) of polyacrylic acid SAP particles, 1.2% (6.2kg) of polycarboxylate superplasticizer, 1000kg of 5-20mm continuously graded crushed stone, 620kg of zone II medium sand (fineness modulus 2.8), 50kg of pre-wetted zeolite sand (replacing 8% of natural sand), and 125kg of water, with a water-cement ratio of 0.24.

[0029] Example 7

[0030] The traditional method for preparing concrete for PHC (Protected Hybrid Cemented Concrete) pipe piles includes the following steps: S1: Dry mixing: Add crushed stone and natural sand to the mixer and dry mix for 30 seconds; S2: Main mixing: Then add P·O52.5 grade silicate cement, S105 grade slag powder, grade I fly ash, silica fume, calcium formate, water-reducing agent and mixing water in sequence, and mix for 120 seconds.

[0031] The resulting mix proportion is: (based on a total cementitious material content of 100%, the total cementitious material content is taken as 520 kg / m³). 3Concrete with a water-cement ratio of 0.24, consisting of 55% (286kg) P·O52.5 grade silicate cement, 25% (130kg) S105 grade slag powder, 15% (78kg) grade I fly ash, 5% (26kg) silica fume, 1.0% (5.2kg) calcium formate, 1.2% (6.2kg) polycarboxylate superplasticizer, 1000kg 5-20mm continuously graded crushed stone, 670kg II zone medium sand (fineness modulus 2.8), and 125kg water.

[0032] Then, the concrete prepared in S2 is used to obtain PHC pipe piles using the traditional high-pressure steam curing process. The formed PHC pipe piles are then left to stand for 2 hours, followed by steam curing at 180℃ and 1.0MPa for 8 hours, followed by cooling for 2 hours.

[0033] Finally, the PHC pipe piles made of concrete with different mix proportions from Examples 1 to 7 were subjected to mechanical and durability tests, and the results are shown in Tables 1 and 2. Table 1: Comparison of Mechanical Properties

[0034] Table 2: Comparison of Durability Performance and Environmental Benefits

[0035] In summary, as shown in Tables 1 and 2: Example 4: Compared with Example 1, its 12h compressive strength and 24h compressive strength were significantly reduced, decreasing by 17.6% and 16.1%, respectively. This is mainly because the CSH seeds and nano-CaCO3 in Example 4 failed to achieve uniform dispersion through the carrier, resulting in uneven distribution of nucleation sites and weakening the early hydration acceleration effect, thus proving the importance of preparing nucleation-carrier-based early-strength slurry.

[0036] Example 5: Compared to Example 1, its 24-hour compressive strength is better, but the 7-day and 28-day compressive strengths show weak growth. The 7-day compressive strength is 68.5 MPa, even lower than in Example 4, and the 28-day compressive strength is 80.5 MPa, the lowest among all examples. Simultaneously, the impermeability grade (P8) and frost resistance grade (F100) decrease significantly. This indicates that the lack of continuous water supply from the dual internal curing components leads to insufficient hydration in the later stages of the low water-cement ratio concrete, resulting in a loose internal structure and poor durability. This demonstrates that the internal curing system plays a crucial role in ensuring the long-term performance and durability of concrete.

[0037] Example 6: The 12-hour compressive strength was 36.0 MPa, and the 24-hour compressive strength was 50.5 MPa, both slightly lower than in Example 1. Furthermore, the impermeability grade (P10) and frost resistance grade (F150) also decreased. The main reason for this is that the uncoated SAP absorbs excessive and premature mixing water during the mixing and resting stages. This not only affects the workability of the fresh concrete (reduced spread) but also causes it to lose its water storage capacity when water release curing is required later, significantly reducing the effectiveness of internal curing. This verifies the necessity of salt-environment-responsive core-shell structured SAP microgels for achieving precise and continuous water release during the critical period of cement hydration.

[0038] Example 7: Although the 28-day compressive strength meets the requirements, the 12-hour and 24-hour compressive strengths are significantly lower than those in Example 1, and the use of traditional high-pressure steam curing technology results in higher energy consumption and carbon emissions. This demonstrates that the autoclaving-free system of the present invention achieves rapid early strength development while also possessing significant energy-saving and environmental protection advantages.

[0039] In summary, this invention, through the synergistic effect of nucleation-carrier early-strength slurry, dual internal curing components, and salt-environment-responsive SAP microgels, along with an optimized stepwise mixing process, constitutes a complete technical system of accelerated nucleation, rapid hydration, slow water release, and structural densification. The absence of any key component or process step will lead to a significant decline in one or more aspects of concrete performance, such as early strength, later strength growth, or long-term durability.

[0040] The above descriptions are merely embodiments of the present invention, and common knowledge regarding specific structures and characteristics is not elaborated upon here. It should be noted that those skilled in the art can make various modifications and improvements without departing from the structure of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the present invention or the practicality of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.

Claims

1. A type of non-autoclaved PHC pipe pile using concrete, characterized in that, The raw materials include cementitious materials, aggregates, composite early-strength components, dual internal curing components, mixing water, and admixtures; the cementitious materials, by mass percentage, include: 50-60% P·O52.5 grade Portland cement, 20-30% S105 grade slag powder, 10-20% Grade I fly ash, and 5-8% silica fume; the aggregates include coarse aggregates and fine aggregates, wherein the coarse aggregates are 5-20mm continuously graded crushed stone, accounting for 40-45%, and the fine aggregates are Zone II medium sand with a fineness modulus of 2.6-3.0, accounting for 25-30%; the composite early-strength... The components, based on the total amount of cementitious materials, include: 0.2-0.8% CSH seed crystals, 0.5-2.0% nano-CaCO3, 3-8% CSA clinker powder, and 0.5-1.5% calcium formate; the dual internal curing components, based on the total amount of cementitious materials, include: 0.10-0.25% salt-loaded SAP and 5-12% pre-wetted lightweight fine aggregate to replace natural sand; the mixing water is tap water or clean reclaimed water, with a water-cement ratio of 0.22-0.28; the admixture is a polycarboxylate superplasticizer, accounting for 0.8-1.5% of the total amount of cementitious materials.

2. The non-autoclaved PHC pipe pile concrete according to claim 1, characterized in that, S105 grade slag powder with a specific surface area ≥ 500 m² 2 / kg, Grade I fly ash residue on a 45μm sieve ≤12%, silica fume specific surface area ≥20000m² 2 / kg, SiO2 content in silica fume ≥90%, crushing index of coarse aggregate ≤8%, average particle size of CSH seeds 100-500nm, solid content ≥30%, specific surface area of ​​nano-CaCO3 ≥800m² 2 / kg, CSA clinker powder with a specific surface area ≥450m² 2 / kg, initial setting time ≥25min, calcium formate purity ≥98%, water absorption ratio of salt-loaded SAP in 0.5%~5% CaCl2 solution ≥20g / g, pre-wetted lightweight fine aggregate is ceramic sand or zeolite sand, water absorption rate ≥15% in 24h, water reduction rate of polycarboxylate superplasticizer ≥30%, solid content ≥40%.

3. A method for preparing concrete for non-autoclaved PHC pipe piles, characterized in that, Includes the following steps: S1: Preparation of nucleated carrier-based early strength slurry: First, take 10-20% of the total amount of S105 grade slag powder or grade I fly ash as carrier powder. Then, mix CSH seed crystals, nano CaCO3 with water-reducing agent and part of mixing water using a high-speed disperser. Then add the carrier powder and continue mixing so that the nanoparticles are uniformly attached to the surface of the carrier powder. S2: Preparation of salt environment responsive SAP microgels: First, polyacrylic acid SAP particles are impregnated in sodium alginate solution, then crosslinked and cured with a mixed solution containing 2-4% CaCl2 and 1-3% silica sol. Next, the surface free salts are removed by washing with water, and then dried to obtain polyacrylic acid SAP microgel particles. S3: Lightweight aggregate pre-wetting and interface strengthening treatment: First, soak the lightweight fine aggregate in clean water and drain it until it is saturated and surface dry. Then, mix the saturated surface dry lightweight fine aggregate with S105 grade slag powder and silica fume to make the S105 grade slag powder and silica fume evenly coat the surface of the lightweight fine aggregate to form a dual-function aggregate. S4: Mixing: First, add crushed stone, natural sand and bifunctional aggregate to the mixer and mix for 30 seconds. Then add the nucleating and reinforcing slurry prepared in S1, the remaining cementitious material and the remaining mixing water and continue mixing for 60-90 seconds. Then add the polyacrylic acid SAP microgel particles prepared in S2 and mix for 30-45 seconds before discharging from the mixer to obtain the non-autoclaved PHC pipe pile concrete.

4. The method for preparing concrete for non-autoclaved PHC pipe piles according to claim 3, characterized in that, In S1, based on the total amount of cementitious materials, the mass percentage of CSH seed crystals is 0.2-0.8%, the mass percentage of nano-CaCO3 is 0.5-2.0%, and the mixing water is 30-50% of the total water volume; the speed of the high-speed disperser is 800-1200 rpm, and the stirring time is 2-3 min; after adding the carrier powder, continue stirring for 1-2 min.

5. The method for preparing concrete for non-autoclaved PHC pipe piles according to claim 3, characterized in that, In S2, the particle size of the polyacrylic acid SAP particles is 0.1-0.5 mm, the mass ratio of polyacrylic acid SAP particles to sodium alginate solution is 1:10-1:20, the mass fraction of sodium alginate aqueous solution is 1.0-2.0%, the impregnation time is 10-20 min, the curing time is 3-8 min, the drying temperature is 45-55℃, and the drying time is 8-12 h.

6. The method for preparing concrete for non-autoclaved PHC pipe piles according to claim 3, characterized in that, In S3, the mass percentage of S105 grade slag powder and silicon powder admixture is 5-10% of the total remaining admixture, and the stirring time is 30-45 seconds.

7. The method for preparing concrete for PHC pipe piles without autoclaving as described in claim 3, characterized in that, In S4, the mixing water accounts for 50-70% of the total water volume, the amount of polyacrylic acid SAP microgel particles added is 0.10-0.25% of the total amount of cementitious materials, and the total stirring time is 120-180s.